Determinants of Tourism and Labor on Regional Revenue in Yogyakarta Special Region after Yogyakarta International Airport - RizkyYunanto; NiniekImaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the connection between the growth of tourism and the income generated locally in the Special Region of Yogyakarta, focusing on the period before and after the operation of Yogyakarta International Airport in 2019. The research problem lies in understanding whether the expansion of transportation infrastructure has altered the determinants from Regional Own-Source Revenue (PAD), especially derived from the tourism sector. The objective is to analyze the influence of tourist numbers, tourist attractions, labor force participation rate (LFPR), and the number of restaurants on PAD across five districts/cities. The study employs panel data regression using data from 2013–2024 and the EViews 12 statistical tool. The findings reveal that the amount of tourists consistently exerts a positive and substantial impact on PAD in both periods, though its magnitude declined after the airport’s operation. Tourist attractions, however, became positively and significantly associated with PAD only in the post-airport period, suggesting a stronger role of destination availability in revenue generation. In contrast, LFPR and the total of restaurants show no significant effect on PAD during either period. These findings highlight a structural shift in PAD sources, with tourism remaining relevant but gradually overshadowed by other emerging sectors such as logistics after the airport’s establishment. The study concludes that while the airport contributed to diversifying economic activity, local governments should optimize tourism potential in parallel with new growth sectors to sustain balanced revenue generation